Comparative Osseointegration Outcomes of Titanium vs. Zirconia Implants: A Schematic Assessment with Meta-Analysis of Bone-Implant Contact and Clinical Longevity - Mahvish Jabeen; Mehvish Saleem; Mehr Un Nisa; Mehwish Urooj; Muhammad Haseeb Rana; Misbah Noreen; Aneesa Khalid (Pakistan Journal of Medicine and Dentistry)
Background: Previously, titanium implants were the most widely chosen option because they bond very well with the jawbone and have good strength. On the other hand, zirconia implants are now being used, giving patients improved appearance, better tissue compatibility, and fewer chances of bacterial infection. The review discusses how titanium and zirconia implants perform when placed in human subjects compared to each other in terms of osseointegration, survival rate, bone loss, and clinical outcomes.